Design and optimization of seedling-feeding device for automatic maize transplanter with maize straw seedling-sprouting tray - Wei, Zhang; Zhaojun, Niu; Lianhao, Li; Yongrui, Hou (International Journal of Agricultural and Biological Engineering, 2015)
This research aimed to solve current problems in the process of maize transplanting in China such as large labor intensity, low working efficiency and poor quality. On the basis of the structure of a seedling-sprouting tray made of maize straw and the agronomic requirements of maize production, this study developed a new feeding device for such a sprouting tray, determined the dimensions of the key components in a virtual environment via Solid Edge software and obtained optimal working parameters in combination with Matlab. Some tests on field validation and maize production were conducted as well. The test results showed the importance of the working parameters on an upright degree in descending order (as well as the best working parameters) to be the vertical angle of seedling planting (13.14°), the forward speed of locomotion (0.57 m/s), and the horizontal angle of the seedling box (22.5°). The standard deviation of the field validation was 6.04%, which was within the allowable range to meet the requirements of maize transplanting. Compared with maize transplanting machines (and manual transplanting operations) on the current market, the labor inputs, as well as the rates of spacing and upright degree qualification, omitted planting and the yield using the new feeding device for automatic transplanter with maize straw seedling-sprouting trays increased 0 (6.9%), 0 (3.1%), 0 (4.5%) and 0 (−1.0%), respectively; whereas, the manufacturing cost was reduced by 35.5%. The results can provide a technical basis and reference for subsequent development of automatic transplanters with maize straw seedling-sprouting trays.Keywords: maize, seedling-sprouting tray, automatic maize transplanter, seedling-feeding device, optimizationDOI: 10.3965/j.ijabe.20150806.1113Citation: Zhang W, Niu Z J, Li L H, Hou Y R. Design and optimization of seedling-feeding device for automatic maize transplanter with maize straw seedling-sprouting tray. Int J Agric & Biol Eng, 2015; 8(6): 1－12.